Extreme signal amplitude events in neuromagnetic oscillations reveal brain aging processing across adulthood - Vakorin, Vasily A.; Liaqat, Hayyan; Doesburg, Sam M.; Moreno, Sylvain (Frontiers in Aging Neuroscience, 2025)
IntroductionNeurophysiological activity, as noninvasively captured by electro- and magnetoencephalography (EEG and MEG), demonstrates complex temporal fluctuations approximated by typical variations around the mean values and rare events with large amplitude. The statistical properties of these extreme and rare events in neurodynamics may reflect the limits or capacity of the brain as a complex system in information processing. However, the exact role of these extreme neurodynamic events in ageing, and their spectral and spatial patterns remain elusive. Our study hypothesized that ageing would be associated with frequency specific alterations in the brain’s tendency to synchronize large ensembles of neurons and to produce extreme events.MethodsTo identify spatio-spectral patterns of these age-related changes in extreme neurodynamics, we examined resting-state MEG recordings from a large cohort of adults (n = 645), aged 18 to 89. We characterized extreme neurodynamics by computing sample skewness and kurtosis, and used Partial Least Squares to test for differences across age groups.ResultsOur findings revealed that each canonical frequency, from theta to lower gamma, displayed unique spatial patterns of either age-related increases, decreases, or both in the brain’s tendency to produce extreme neuromagnetic events.DiscussionOur study introduces a novel neuroimaging framework for understanding ageing through the extreme and rare events of the neurophysiological activity, offering more sensitivity than typical comparative approaches.